Fundraisning Strategy in a Nonprofit Organization - Novotný, Jiří; Boukal, Petr, 1962-2022; Kotáb, Jiří; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
This thesis aims to map the history and development of fundraising in the world, particularly in the United States. It also describes the modern theoretical concepts, which are currently being used for the preparation and planning of fundraising strategy. The practical section consists of analysis of the Czech branch of the global organization Transparency International and the evaluation of its fundraising strategy with a focus on individual and corporate donors.
Vedoucí práce: Petr Boukal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses